2011
DOI: 10.1183/09031936.00139810
|View full text |Cite
|
Sign up to set email alerts
|

Airway inflammation is augmented by obesity and fatty acids in asthma

Abstract: Obesity and asthma are associated, but the mechanism(s) of the association have yet to be elucidated. The aim of this study was to assess airway inflammation in relation to obesity and plasma fatty acids in males and females with and without asthma.Obese (n568) and nonobese (n547) adults with asthma, and obese (n516) and nonobese (n563) healthy controls had induced sputum and venous blood samples analysed for inflammatory markers.There was a positive interaction between obesity and asthma on sputum neutrophil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
249
4
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(278 citation statements)
references
References 35 publications
18
249
4
7
Order By: Relevance
“…112,113 Obese asthmatic children did not have elevated airway LTB 4 . 134 Recent adult studies suggest that obesity may enhance neutrophilic airway inflammation 139 and systemic leukotriene production, 140 though this has not been evaluated in children. Since inhaled steroids are generally ineffective against neutrophilic inflammation, the discovery of neutrophilic inflammation in obese asthmatics is consistent with findings of reduced corticosteroids efficacy in the obese.…”
Section: Airway Inflammationmentioning
confidence: 99%
“…112,113 Obese asthmatic children did not have elevated airway LTB 4 . 134 Recent adult studies suggest that obesity may enhance neutrophilic airway inflammation 139 and systemic leukotriene production, 140 though this has not been evaluated in children. Since inhaled steroids are generally ineffective against neutrophilic inflammation, the discovery of neutrophilic inflammation in obese asthmatics is consistent with findings of reduced corticosteroids efficacy in the obese.…”
Section: Airway Inflammationmentioning
confidence: 99%
“…Obese and non-obese children and adults with asthma were recruited from the general community and John Hunter Hospital (Newcastle, Australia) [9,13]. In this study, we assayed stored samples of plasma from these two previously described populations.…”
Section: Subjectsmentioning
confidence: 99%
“…Furthermore, LANG et al [8] found age to be an important effect modifier of asthma control and airway function in obese asthma. Various studies have reported that obese adults with asthma had high levels of C-reactive protein (CRP) [9,10] and markers of macrophage infiltration [11]. Tryptase, a marker of mast cell activation, is also elevated in obese non-asthmatic adults [5].…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of the link between obesity and asthma is unknown, and proposed mechanisms include a proinflammatory effect of obesity and a physiological effect resulting from body composition changes associated with obesity (4,6). Additionally, there appear to be gender-specific differences in the mechanisms (7).…”
mentioning
confidence: 99%